Peningkatan Kapasitas Satuan Perlindungan Masyarakat (Satlinmas) di Kelurahan Pucangsawit Kecamatan Jebres Kota Surakarta - Joko Pramono; Joko Suranto (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
Capacity building in modern organizations is an unavoidable necessity. Capacity development is one of the strategies that can be carried out in achieving organizational goals and to enable organizations to grow stronger in achieving their goals and missions. Capacity building within the organization of the Community Protection Unit (Satlinmas) is also a necessity. This is related to the existence of Satlinmas members as personnel who are expected to be able to carry out an auxiliary role in the implementation of community protection. One of the important capacities possessed is related to disasters, related to early detection of potential disasters, to the role of assistance that can be carried out in first aid in disaster events. Looking at the development and dynamics of the City of Surakarta, it is proper to have a Satlinmas with a capable capacity. Thus, support for the implementation of community protection can be optimal. So the need for human resource capacity development in Satlinmas must be carried out. This capacity development must be able to meet the needs of Satlinmas members in carrying out their duties. To achieve these goals, it is necessary to formulate several aspects in order to map the portion of human resource development needed. Aspects of capacity building at the individual level that emphasize human resources at Satlinmas, include several aspects in the form of: knowledge and competence; training; work ethic; recruitment, termination and utilization; Payroll; and workplace conditions